1984
DOI: 10.1002/pd.1970040310
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C induced chromosome damage in fetal blood cultures and prenatal diagnosis of fanconi's anaemia

Abstract: We report the use of fetal blood for the prenatal diagnosis of Fanconi anaemia (FA). The clastogenic action of Mitomycin C (MMC) is compared in blood cultures from different fetuses, normal controls and FA heterozygotes. The fetus at risk is shown to suffer from FA on the grounds of excessive chromosome breakage, both spontaneous and MMC induced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The cases of prenatal diagnosis presented in this paper mostly belong to the categories I and II. Whereas most laboratories performing prenatal diagnosis of FA employ chromosome breakage studies after exposure to DNA-cross-linking agents [17][18][19] , the data presented in this paper suggests that fl ow cytometry is an alternative functional assay. Flow cytometry testing has the advantage of speed and circumvents the problem of poor or insuffi cient metaphase yields from sparse or poorly growing AF cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The cases of prenatal diagnosis presented in this paper mostly belong to the categories I and II. Whereas most laboratories performing prenatal diagnosis of FA employ chromosome breakage studies after exposure to DNA-cross-linking agents [17][18][19] , the data presented in this paper suggests that fl ow cytometry is an alternative functional assay. Flow cytometry testing has the advantage of speed and circumvents the problem of poor or insuffi cient metaphase yields from sparse or poorly growing AF cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…For several years, cytogenetic methods looking for hypersensitivity to M M C or DEB (Auerbach et al, 1981(Auerbach et al, , 1985Cervenka et al, 1981;Shipley et al, 1984) were the only methods available for both prenatal and postnatal diagnosis of FA. The gene for F A complementation group C has been cloned (Strathdee et al, 1992a) and a number of pathogenic mutations have been identified in this gene (Verlander et al, 1994;Whitney et al, 1993).…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…Very important, on the contrary, is prenatal diagnosis because parents of a patient, at each new pregnancy, have a 1 in 4 risk of producing an affected child. Direct prenatal diagnostic tests are already available for such diseases (Ramsay et al 1974;Giannelli et al 1982a;Auerbach et al 1981;Shipley et al 1984;Lehmann et al 1985), but the analysis of the familial segregation of DNA polymorphisms could be a useful addition.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…radiation, spontaneous levels of sister chromatid exchanges, X-ray sensitivity and sensitivity to bifunctional alkylating agents have been used for postnatal, and even prenatal, diagnosis (Kawai et al 1983;Lehmann et al 1985;German, 1979;Giannelli et al 1982«;Coxetal. 1978;Auerbach et al 1981;Shipley et al 1984).…”
Section: Other Diseases With Clear Hypersensitivity To Dna-damaging Tmentioning
confidence: 99%